Crystal growth, crystal structure and pyroelectric properties of the polar hexagonal antimony tartrates MII[Sb2(C4H2O6)2]·2H2O (MII = Ca, Sr, Pb). Issue 6 (3rd May 2015) - Bohatý, Ladislav; Held, Peter; Schneeberger, Helmut; Zheng, Tianyi; Becker, Petra
<x xml:space="preserve">Abstract</x> Large single crystals of the hexagonal antimony tartrates of calcium, strontium and, particularly new, of lead have been grown from hot aqueous solutions. Structural investigations of all three compounds confirm the isomorphism of these non‐ferroelectric polar crystals. The pyroelectric coefficients of the calcium and of the strontium compound are comparable to those of tourmaline.